(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
In the article, it is planned to build small and medium-sized hydroelectric power stations and irrigation canals in our country. A comprehensive solution to the problems in this field of construction is provided by large-scale industrialization of construction processes.